Development of the football bounce game model as a physical education learning medium at senior high school 4, gorontalo city - Gusti Tahir; Risna Podungge; Sulasikin Sahdi Kadir (Gorontalo State University, 2025)
Physical education, sport, and health (PJOK) learning in Indonesian senior high schools continues to face the problem of declining student interest in physical activity, particularly when instruction relies on repetitive, conventional drills rather than engaging game-based media. This study addresses that gap by developing Football Bounce, a modified game that adapts the ball-bouncing principle of sepak takraw to a badminton-court configuration, as a creative and inclusive medium for PJOK learning. This research and development (RD) study used the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation questionnaires completed by a game/product expert and a learning expert, and through a response questionnaire administered to 30 twelfth-grade students following a small-scale field trial. Data were analyzed descriptively using a four-point Likert scale converted into eligibility percentages. The game expert rated the product 88.63% (strongly agree) at the initial validation stage and 88.68% after revision; the learning expert rated it 80.76% initially and 93.3% after revision; and the student trial produced a total response score of 88.41%, all within the “strongly agree/very feasible” category. These findings indicate that the Football Bounce game model is valid, practical, and effective as a physical education learning medium capable of enhancing students’ motivation, fitness, and fundamental game skills, and that it offers a novel, low-cost, badminton-court-based alternative for wider community use.